2016
DOI: 10.7603/s40681-016-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Solitary renal metastasis of esophageal squamous cell carcinoma mimicking primary renal neoplasm – A case report and literature review

Abstract: Solitary renal metastasis of esophageal cancer is rare clinically, with only 14 cases being reported in the literature. The authors here report a case of a 53-year-old man with a metachronous hypopharyngeal and esophageal squamous cell carcinoma who developed a solitary renal metastasis after complete chemoradiotherapy for esophageal cancer, and subsequently received a left nephrectomy. The metastatic esophageal cancer was indistinguishable from primary renal neoplasm in the computed tomography but showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Gastric metastasis from EC is very rare, with an incidence of 1%−4.58% in clinical practice, and is often found accidentally during autopsy or surgery ( 14 ). Renal metastasis from EC is also rare, with an overall survival of 2 months to 9 years after nephrectomy with or without adjuvant chemotherapy ( 15 ). Studies have shown that the incidence of bone metastases from EC is 2%−6%, with a mean survival time of 4 months after the first detection of sclerosing lesions ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric metastasis from EC is very rare, with an incidence of 1%−4.58% in clinical practice, and is often found accidentally during autopsy or surgery ( 14 ). Renal metastasis from EC is also rare, with an overall survival of 2 months to 9 years after nephrectomy with or without adjuvant chemotherapy ( 15 ). Studies have shown that the incidence of bone metastases from EC is 2%−6%, with a mean survival time of 4 months after the first detection of sclerosing lesions ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings showed that squamous cell carcinoma is more likely to metastasize to the kidney than to other locations. [ 8 ] Metastases of esophageal cancer to the kidney are considered to be very rare, especially unilateral isolated renal metastases. [ 9 ] Upon imaging, it is difficult to distinguish whether the tumor represents primary renal pelvis transitional cell carcinoma or metastatic renal pelvis carcinoma because both diseases show infiltrative growth into the renal parenchyma and multiple protrusions into the renal tissue, and some cases are accompanied by invasion of the perirenal fat or perirenal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The present case in addition to the other 11 previously reported cases of esophageal cancer with renal metastasis and their treatment are briefly summarized in Table 1. 8,[12][13][14][15][16][17][18][19][20] Some cases had undergone surgical treatment because the differentiation between metastasis and primary renal tumor was difficult. Others were treated with surgical resection followed by chemotherapy and showed longer survival than those received surgical treatment alone, although this difference was not statically significant.…”
Section: Discussionmentioning
confidence: 99%